Etika Komunikasi Islam Dalam Manajemen Komunikasi Organisasi - Aisyah Shofwatu Auliya; Laras Puspitasari; Ismail Mubarok (Jurnal Pendidikan Indonesia, 2023)
The success and continuity of an organization depends on good communication management. In this situation, Islamic communication ethics becomes an important framework that can direct communication in an organization. First, the principle of unity (adab) is the basis of Islamic communication ethics. Unity of communication encompasses many things, including the manners in which it is spoken, therefore, in organizational communication management, it is very important to create an environment based on politeness where everyone working in the organization feels valued and respected. Unity is the key to interacting with others in a good and productive way within the organization. The two main principles of Islamic communication ethics are honesty and transparency. Honesty in communication and transparency in decision-making should be the basis of ethical communication management in organizations. These principles help build trust among the organization and ensure that the information documented is reliable. Therefore, the integration of organizational communication depends on honesty and transparency. In addition, Islamic communication ethics emphasize the importance of listening attentively and experiencing the feelings of others. The ability to understand others’ views and feelings is necessary for effective communication managers. By listening, communication managers can create an environment where every voice is valued. This improves communication and relationships between organizational members. Islamic communication ethics offers a justice- and mercy-based approach to conflict management. Communication managers should manage conflicts in a fair way and prioritize the values of grace so that conflicts can be resolved peacefully and produce benefits for the company.